Analysis and Protection for Information Security Event of Communication Industry User - Rong Wang; Hong Li; Xuan Jin (Dianxin kexue)
Some security incidents of user information were analyzed and the existent leaks were studied,the cause of the problem was summarized.The solution was put forward by analyzing from several aspects,like the user information protection,security technical means,sentimental information protection,security management system.Some constructive opinions and suggestions for the establishment of communication industry user information security system were put forward.It is practical and valuable for communication industry.